Pizza prime / Farid Iqmal Hanizam ...[et al.] - Hanizam, Farid Iqmal; Baharuddin, Muhammad Hafizuddin; Ramlan, Muhamad Rusydi; Ismail, Muhammad Shahir (2022)
Assisting career housewives in cooking new meals by saving time. To entice new customers, a new sort of pizza concept is being introduced. Expand our business to all around Malaysia Frozen pizza into international market.